Simultaneous electrochemical determination of dopamine, uric acid and ascorbic acid using palladium nanoparticle-loaded carbon nanofibers modified electrode - Huang, J.; Liu, Yang; Hou, H.; You, T. (Elsevier BV, 2008)
Palladium nanoparticle-loaded carbon nanofibers (Pd/CNFs) were prepared by electrospinning and subsequent thermal treatment processes. Pd/CNFs modified carbon paste electrode (Pd/CNF-CPE) displayed excellent electrochemical catalytic activities towards dopamine (DA), uric acid (UA) and ascorbic acid (AA). The oxidation overpotentials of DA, UA and AA were decreased significantly compared with those obtained at the bare CPE. Differential pulse voltammetry was used for the simultaneous determination of DA, UA and AA in their ternary mixture. The peak separation between UA and DA, DA and AA was 148 mV and 244 mV, respectively. The calibration curves for DA, UA and AA were obtained in the range of 0.5–160 μM, 2–200 μM, and 0.05–4 mM, respectively. The lowest detection limits (S/N = 3) were 0.2 μM, 0.7 μM and 15 μM for DA, UA and AA, respectively. With good selectively and sensitivity, the present method was applied to the determination of DA in injectable medicine and UA in urine sample.